Heparin‐induced thrombocytopenia in a hemodialysis patient treated with fondaparinux: Nephrologists between two fires. Issue 2 (28th May 2012) - Solak, Yalcin; Demircioglu, Sinan; Polat, Ilker; Biyik, Zeynep; Gaipov, Abduzhappar; Acar, Kadir; Turk, Suleyman
Abstract: Heparin‐induced thrombocytopenia (HIT) is caused by heparin exposure and presents with reduced platelet count. Patients undergoing hemodialysis (HD) treatment have increased risk of developing HIT due to prolonged exposure to unfractionated heparin or low‐molecular weight heparin. We report a 79‐year‐old male patient with end‐stage renal disease who developed type‐II HIT during maintenance HD. Platelet count of the patient decreased gradually and antiplatelet factor IV antibody was found to be positive. The patient was treated with fondaparinux and continued heparin‐free HD. Unfortunately, despite favorable initial response without any thrombotic episodes, the patient died due to severe sepsis complicated by gastrointestinal hemorrhage.